O construtivismo kantiano na teoria da justiça como equidade de John Rawls - Ferreira, Samir Dessbesel (2006)
The dissertation has as a principal aim to approach the argumentative model in moral philosophy named by Rawls in terms of kantian constructivism, in order to explain the use that Rawls does of this model in his own theory, the theory of justice as fairness. To do it, Its is initially searched for a general characterization of the constructivist model and its kantian variant to enlighten that the distinctive part of the kantian constructivist resides in the notion of moral person, free and equal, used in its construction procedure. In Rawl s interpretation of Kant practical philosophy, it is found an enlightened application of the constructivist model in terms of presenting several common aspects in comparison to the theory of justice as fairness. In this perspective, the work focuses on the analysis of the principal resource that Rawls uses to justify his principles of justice, the original position. This as a procedure of construction inspired in the classic contractarianism establishes a set of limitations about the deliberation of agents ideally conceited. As Rawls searches to present a justification to these limitations, he is supported by a form of coherent argument, what compromise the intended neutrality of the procedure, in terms of its justificatory status. Considering the specific demands of a political concept of justice as well as the notion of justification associate to it, the work aims to explain which function executes the original position in the justice theory as equity as the constructivism kantian is presented as a model of justification.